Hydration and Cooling Practices Among Farmworkers in Oregon and Washington. Issue 3 (3rd July 2017) - Bethel, Jeffrey W.; Spector, June T.; Krenz, Jennifer
ABSTRACT: Objectives: Although recommendations for preventing occupational heat-related illness among farmworkers include hydration and cooling practices, the extent to which these recommendations are universally practiced is unknown. The objective of this analysis was to compare hydration and cooling practices between farmworkers in Oregon and Washington. Methods: A survey was administered to a purposive sample of Oregon and Washington farmworkers. Data collected included demographics, work history and current work practices, hydration practices, access and use of cooling measures, and headwear and clothing worn. Results: Oregon farmworkers were more likely than those in Washington to consume beverages containing sugar and/or caffeine. Workers in Oregon more frequently reported using various cooling measures compared with workers in Washington. Availability of cooling measures also varied between the two states. Conclusions: These results highlight the large variability between workers in two states regarding access to and use of methods to stay cool while working in the heat.